Luminescence Properties of Dy3+-Doped CaLaP3O10 White-Light Phosphors Under Vacuum Ultraviolet Excitation - Zhang, Li; Cai Han, Guo (Asian Journal of Chemistry, 2014)
New Dy3+-doped CaLaP3O10 white light phosphors were satisfactory synthesized by solid phase reaction. The luminescence properties of the CaLa1-xP3O10:xDy3+ under vacuum ultraviolet (VUV) excitation were investigated. The emission spectra show that the phosphors can efficiently emit blue light and yellow light and finally obtain white light. The excitation spectrum monitored at 572 nm indicates that the samples can efficiently absorb vacuum ultraviolet light from 100 to 300nm with the strongest peak at about 172 nm and the energy can transfer to the levels of Dy3+ ion from the host materials. Moreover, the white light phosphors materials are activated by a Dy3+ ion and the luminescence of CaLa1-xP3O10:xDy3+ under vacuum ultraviolet excitation was effective. Therefore, it may have the promising of being applied to mercury-free fluorescence lamp.